2019
DOI: 10.1007/978-3-030-30244-3_1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age and Gender in the Interaction with Touch Screens

Abstract: Touch screens are nowadays one of the major interfaces in the interaction between humans and technology, mostly due to the significant growth in the use of smartphones and tablets in the last years. This broad use, that reaches people from all strata of society, makes touch screens a relevant tool to study the mechanisms that influence the way we interact with electronic devices. In this paper we collect data regarding the interaction patterns of different users with mobile devices. We present a way to formali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The survey results indicate partial support for Hypothesis 4 . This study's finding is consistent with the survey conducted by Rocha, Carneiro, & Novais (2019), which found that females outperformed males in touch decision time and duration during touchscreen interactions [ 82 ].…”
Section: Discussionsupporting
confidence: 91%
“…The survey results indicate partial support for Hypothesis 4 . This study's finding is consistent with the survey conducted by Rocha, Carneiro, & Novais (2019), which found that females outperformed males in touch decision time and duration during touchscreen interactions [ 82 ].…”
Section: Discussionsupporting
confidence: 91%